Prospective Physics Teachers' Perceptions of an Objective Structured Teaching Examination (OSTE) - Vogelsang, Christoph; Grotegut, Lea; Wotschel, Philipp; Janzen, Thomas
In higher education, assessment/examination procedures should be designed to form a coherent learning process that is aligned with the intended learning objectives and planned learning activities. However, in academic teacher education programmes often use assessment formats that are not well aligned with the demands of teachers' actual professional practice. Performance-based assessments can offer an alternative, for example in the form of role-play-based simulations with trained actors representing typical professional activities in environments of reduced complexity. We have developed such a performance-based assessment format for physics teacher education, analogous to the Objective Structured Teaching Examinations (OSTE) approach used in medical education. The OSTE prototype consists of seven short simulative assessments, reflecting four areas of competence (Instruction, Assessment, Pedagogy and Innovation) that form a 90-minute examination course. In order to investigate prospective physics teachers' perceptions of such an assessment format in terms of its suitability as a summative examination procedure, we piloted the OSTE prototype with N = 34 physics student teachers from three German universities using short questionnaires. The results show that participants perceived the OSTE prototype as authentic and relevant, but they also highlight the need for adequate new learning opportunities to prepare for such simulative examinations to be integrated into teacher education programmes.
Keywords: teacher education; physics; assessment; pre-service teachers

„als Student hätte ich da mehr Bock drauf als auf eine [Fachdidaktikklausur]“ - Die Wahrnehmung von Studierenden hinsichtlich rollenspielbasierter Simulationen als handlungsorientiertes Prüfungsformat für die Englischlehrkräftebildung - Janzen, Thomas; Wotschel, Philipp; Grotegut, Lea; Vogelsang, Christoph

Validierung einer rollenspielbasierten Simulationsprüfung für angehende Englischlehrkräfte- Validitätsargumente zum Scoring und zur Testwertinterpretation - Janzen, Thomas; Grotegut, Lea; Wotschel, Philipp; Vogelsang, Christoph

Auf die Prüfung kommt es an! - Handlungsnahe Prüfungsformate in Lehramtsstudiengängen - Vogelsang, Christoph; Wotschel, Philipp; Janzen, Thomas; Grotegut, Lea

Das Handeln prüfen - Performanzorientierte Prüfungsformate im Lehramtsstudium - Vogelsang, Christoph; Wotschel, Philipp; Janzen, Thomas; Grotegut, Lea

Thoughts Are Free—Differences Between Unstructured and Structured Reflections of Teachers with Different Levels of Expertise - Vogelsang, Christoph; Scholl, Daniel; Meier, Jana; Küth, Simon (Education Sciences)

Musterhaftigkeit und Formen sprachlicher Kreativität im Kontext der Annotation argumentativer Lerner:innentexte - Rezat, Sara; Karabey, Rabia (Sprachliche Kreativität in Bildungs- und Fachsprache: Textproduktion und Diskurspraktiken)

Introduction: Irish Communities in a Glocal Context – Literary and Cultural Narratives - Strauß, Sara (Anglistik: International Journal of English Studies)

Focus on Irish Communities in a Glocal Context: Literary and Cultural Narratives (Anglistik: International Journal of English Studies)

Technische Grundbildung im Elementar- und Primarbereich gestalten – Evidenzbasierte Entwicklung spiralcurricularer Lernangebote zur Förderung von Problemsolving integrating Computational Thinking (PiCT) - Schemel, Nele; Schröer, Franz; Tenberge, Claudia (Mitwelt im Wandel wahrnehmen, verstehen und gestalten)

Morphological Degradation of Oxygen Evolution Reaction-Electrocatalyzing Nickel Selenides at Industrially Relevant Current Densities - Hiege, Felix; Chang, Chun-Wai; Trost, Oliver; van Halteren, Charlotte E. R.; Hosseini, Pouya; Bendt, Georg; Schulz, Stephan; Feng, Zhenxing; Linnemann, Julia; Tschulik, Kristina (ACS Applied Materials & Interfaces)
We investigated electrodeposited nanoparticulate nickel selenide (pre)catalysts that transform into nickel oxides/oxyhydroxides under oxygen evolution reaction conditions in alkaline solutions. Previous studies of this transformation were conducted at lower current densities than those of industrial relevance (≥1 A cm–2). We used ultramicroelectrodes (UMEs) to achieve such current densities, benefiting from their small size, ensuring low absolute currents and low ohmic drop but high current densities. Morphological degradation of the catalyst material was only observed at current densities exceeding 1 A cm–2 but not for smaller ones. Using X-ray absorption, X-ray photoemission spectroscopy, and X-ray diffraction, we confirmed that the degradation was accompanied by the literature-known transformation of nanoparticulate Ni3Se2 (bulk)/NiSe (surface) into nickel oxyhydroxide. The transformation of the precatalyst goes along with a significant improvement in the charge transfer kinetics observed by decreasing Tafel slopes with ongoing experimental time extracted from cyclic voltammetry (CV) experiments and electrochemical impedance spectroscopy (EIS) in the high-frequency range. However, these kinetic improvements are accompanied by limitations in mass transport concluded from decreasing current responses at high overpotentials in CVs and increasing impedance in the low-frequency range of the EIS spectra after extended CV cycling. These mass transport limitations originated from morphological degradations at the UME exceeding 1 A cm–2 which we proved by applying identical location scanning electron microscopy. This has not been reported in studies that have been limited to lower current densities before. Our findings showcase how UMEs can be used to study (pre)catalysts (herein nickel selenides) under current densities of industrial relevance in the absence of ohmic drop-related ambiguities, combined with in-depth materials characterization studies, e.g., identical location microscopy and advanced spectroscopic methods. This approach enables direct evaluation and comparison of catalyst materials and thus demonstrates how to overcome long-standing limitations of electrocatalyst design and testing.
Keywords: Electrocatalysis; oxygen evolution reaction; nickel selenide; microelectrode

Water-assisted proton conductivity and a magnetic study of heterotrinuclear oxalate-bridged compounds: molecular precursors for the Mn2CrO4 spinel - Lozančić, Ana; Burazer, Sanja; Wagner, Tobias; Molčanov, Krešimir; Pajić, Damir; Androš Dubraja, Lidija; Tiemann, Michael; Jurić, Marijana (Journal of Materials Chemistry C)
Novel oxalate-bridged heterotrinuclear complexes [A][Mn2Cr(bpy)2(H2O)2Cl2(C2O4)3] (A = (CH3)2(C2H5)NH+ (1) and (CH3)(C2H5)2NH+ (2); bpy = 2,2′-bipyridine) were synthesized using an aqueous solution of [A]3[Cr(C2O4)3] as a building block in reaction with Mn2+ ions and with the addition of the N-donor ligand bipyridine. The isostructural heterometallic complex salts were characterized by single-crystal and powder X-ray diffraction, infrared and impedance spectroscopy, thermal analysis and magnetization measurements. The trinuclear anion [{Mn(bpy)(H2O)Cl(μ-C2O4)}2Cr(C2O4)]− consists of two [Mn(bpy)(H2O)Cl]+ units bridged by the [Cr(C2O4)3]3− anion, which acts as a bidentate ligand towards each of the manganese atoms. The anions are hydrogen bonded to each other via coordinated chloride anions, water molecules and oxygen oxalate atoms, resulting in two-dimensional (2D) hydrogen bonding layers. Compounds exhibit water-assisted proton conductivity behaviour, which was investigated at different temperatures and relative humidities (RH). At 25 °C, an increase in RH from 60% to 93% resulted in an obvious proton conducting switch from 9.1 × 10−11 to 5.6 × 10−5 S cm−1 for 1 and from 7.4 × 10−10 to 1.8 × 10−6 S cm−1 for 2, corresponding to high on/off ratios of about 106 for 1 and 104 for 2. In situ powder X-ray diffraction (PXRD) analysis showed that unit cell parameters of compounds 1 and 2 slightly increase when exposed to humid conditions. This confirmed that incorporation of water molecules into structures with pores and voids causes the proton conductivity switching phenomenon. Magnetic susceptibility measurements indicate a ferromagnetic interaction between Cr3+ and Mn2+ ions bridged by the bis(bidentate) oxalate group. The prepared compounds 1 and 2 were explored as single-source precursors for the formation of spinel oxide by their thermal treatment. With increasing temperature, the spinel composition changed according to the formula Mn1+xCr2–xO4 (0 ≤ x ≤ 1), where x = 0.7 at 500 °C and x = 1 at 900 °C when tet[MnII]oct[MnIIICrIII]O4 is formed. The (micro)structure, morphology, and optical properties of spinel Mn2CrO4 were characterized by PXRD, scanning electron microscopy and UV-Vis diffuse reflectance spectroscopy. The photocatalytic activity of this oxide in degradation of the methylene blue dye under Vis irradiation without and with the support of hydrogen peroxide was further investigated.

Fast‐Responding O2 Gas Sensor Based on Luminescent Europium Metal‐Organic Frameworks (MOF‐76) - Zhao, Zhenyu; Weinberger, Christian; Steube, Jakob; Bauer, Matthias; Brehm, Martin; Tiemann, Michael (Advanced Functional Materials)
The increasing demand for advanced sensing technologies drives the development of chemical sensors using innovative materials. In gas sensing, optical sensors are often used to detect gases such as CO, NOx, and O2. Oxygen sensors typically incorporate dyes into oxygen-permeable matrices like polymers, silica, or zeolites. Alternatively, semiconductor surface chemistry can enable O2 detection. However, these approaches are often limited by slow response and recovery times and low selectivity, restricting their practical applications. The metal-organic framework MOF-76(Eu) and its yttrium-modified variant, MOF-76(Eu/Y) are reported to exhibit highly reversible and fast optical responses to varying O2 concentrations. Time-resolved emission measurements are performed over short (seconds) and long (hours) timescales using N2 and synthetic air mixtures. Cross-sensitivity to humidity is analyzed. Multichannel scaling photon-counting experiments confirm quenching at the linker level, as the emission lifetime remains nearly constant. Yttrium significantly improves stability and performance at room temperature. Structural and optical changes induced by yttrium are investigated. Additionally, MIL-78(Eu), another Eu-BTC-based MOF with a different coordination environment, is synthesized. Unlike MOF-76(Eu), MIL-78(Eu) exhibits distinct optical properties but lacks a reversible response to O2. These results highlight the potential of MOF-76-based materials for high-performance O2 sensing.

Ethical dilemmas in coaching: Diversity and inclusion and the role of the coach - Radtke, Sabine
Keywords: Sports Coaching; Diversity; Intersectionality

Disaggregation at High Volume Exclusion: An “Overcrowding” Effect - Koch, Leon; Baier, Dominik; Rajput, Satyendra; König, Benedikt; Tiemann, Michael; Ebbinghaus, Simon; Nayar, Divya; Huber, Klaus (The Journal of Physical Chemistry B)

Innovative teaching with actionbound: Digital pathways in chemistry education - a practical example from ComeNet Chemistry in the ComeMINT Project - Weiser, David; Ditter, Rebecca; Ditter, David; Siepmann, Karin; Grandrath, Rebecca; Fechner, Sabine; Sommer, Katrin; Bohrmann-Linde, Claudia; Rubner, Isabel (International conference New Perspective on Science Education)

Empirische Befunde der Interessenforschung der Fächer Biologie, Chemie und Physik im Primar- und Sekundarbereich seit 2012 – Ein systematisches Review - Habig, Sebastian; Großmann, Nadine; Schmid, Andrea M.; van Vorst, Helena; Fechner, Sabine; Wilde, Matthias (Interesse revisited)

Interessenförderung im Physik- und Chemieunterricht – Eine Bestandsaufnahme - Zöchling, Sarah; Pletschacher, Laura; Maurer, Christian; Berger, Roland; Lindmaier, Kerstin; Fechner, Sabine; Wodzinski, Rita (Interesse revisited)

Parameter Averaging in Link Prediction - Sapkota, Rupesh; Demir, Caglar; Sharma, Arnab; Ngonga Ngomo, Axel-Cyrille (Proceedings of the Thirteenth International Conference on Knowledge Capture(K-CAP 2025))
Ensemble methods are widely employed to improve generalization in machine learning. This has also prompted the adoption of ensemble learning for the knowledge graph embedding (KGE) models in performing link prediction. Typical approaches to this end train multiple models as part of the ensemble, and the diverse predictions are then averaged. However, this approach has some significant drawbacks. For instance, the computational overhead of training multiple models increases latency and memory overhead. In contrast, model merging approaches offer a promising alternative that does not require training multiple models. In this work, we introduce model merging, specifically weighted averaging, in KGE models. Herein, a running average of model parameters from a training epoch onward is maintained and used for predictions. To address this, we additionally propose an approach that selectively updates the running average of the ensemble model parameters only when the generalization performance improves on a validation dataset. We evaluate these two different weighted averaging approaches on link prediction tasks, comparing the state-of-the-art benchmark ensemble approach. Additionally, we evaluate the weighted averaging approach considering literal-augmented KGE models and multi-hop query answering tasks as well. The results demonstrate that the proposed weighted averaging approach consistently improves performance across diverse evaluation settings.
Keywords: Knowledge Graphs; Embeddings; Ensemble Learning

Kindermädchen – Von ‚strebsamen Mädchen‘, fliegenden Regenschirmen und neuen Gewändern eines (nicht) ausgestorbenen Berufes - Göddertz, Nina (Soziale Frauenberufe in Ost und West)